Technical Considerations of Phosphorous-32 Bremsstrahlung SPECT Imaging after Radioembolization of Hepatic Tumors: A Clinical Assessment with a Review of Imaging Parameters - Elahe Pirayesh; Mahasti Amoui; Shahram Akhlaghpoor; Shahnaz Tolooee; Maryam Khorrami; Hossain PoorBeigi; Shahab Sheibani; Majid Assadi (Radiology Research and Practice)
Background. Bremsstrahlung (BS) imaging during radioembolization (RE) confirms the deposition of radiotracer in hepatic/extrahepatic tumors. The aim of this study is to demonstrate 32P images and to optimize the imaging parameters. Materials and Methods. Thirty-nine patients with variable types of hepatic tumors, treated with the intra-arterial injection of 32P, were included. All patients underwent BS SPECT imaging 24–72 h after tracer administration, using low energy high resolution (LEHR) (18 patients) or medium energy general purpose (MEGP) (21 patients) collimators. A grading scale from 1 to 4 was used to express the compatibility of the 32P images with those obtained from CT/MRI. Results. Although the image quality obtained with the MEGP collimator was visually and quantitatively better than with the LEHR (76% concordance score versus 71%, resp.), there was no statistically significant difference between them. Conclusion. The MEGP collimator is the first choice for BS SPECT imaging. However, if the collimator change is time consuming (as in a busy center) or an MEGP collimator is not available, the LEHR collimator could be practical with acceptable images, especially in a SPECT study. In addition, BS imaging is a useful method to confirm the proper distribution of radiotherapeutic agents and has good correlation with anatomical findings.